Supplemental Food Production With Plants: A Review of NASA Research - Johnson, Christina M.; Boles, Haley O.; Spencer, LaShelle E.; Poulet, Lucie; Romeyn, Matthew; Bunchek, Jess M.; Fritsche, Ralph; Massa, Gioia D.; O’Rourke, Aubrie; Wheeler, Raymond M. (Frontiers in Astronomy and Space Sciences, 2021)
Bioregenerative life support systems for space have been investigated for 60 years, and plants and other photosynthetic organisms are central to this concept for their ability to produce food and O2, remove CO2, and help recycle wastewater. Many of the studies targeted larger scale systems that might be used for planetary surface missions, with estimates ranging from about 40 to 50 m2 (or more) of crop growing area needed per person. But early space missions will not have these volumes available for crop growth. How can plants be used in the interim, where perhaps < 5 m2 of growing area might be available? One option is to grow plants as supplemental, fresh foods. This could improve the quality and diversity of the meals on the International Space Station (ISS) or on the Lunar surface, and supply important nutrients to the astronauts for missions like Mars transit, and longer duration Martian surface missions. Although plant chambers for supplemental food production would be relatively small, they could provide the bioregenerative research community platforms for testing different crops in a space environment and serve as a stepping stone to build larger bioregenerative systems for future missions. Here we review some of NASA’s research and development (ground and spaceflight) targeting fresh food production systems for space.